DEVELOPMENT OF WATER DISTRIBUTION AND WATER VOLUME PRACTICUM TOOLS USING THE YF-S401 FLOW SENSOR ON DYNAMIC FLUID MATERIALS IN SENIOR HIGH SCHOOL - Fitria Rahmawati, Desti; Hamdani, Dedy; Putri, Desy Hanisa (Jurnal Pendidikan Matematika dan IPA, 2023)
This study aims to: 1) develop practical teaching aids for discharge and water volume using a flow sensor YF-S401 and Arduino Uno, 2) determine the feasibility of teaching aids, and 3) determine students' perceptions of the teaching aids that have been made. developed. The research method used is Research and Development with the ADDIE model which includes Analysis, Design, Development, Implementation, and Evaluation. However, the research and development carried out is still limited to the development stage. The instruments used in this study were: 1) media expert and material expert validation sheets to test the feasibility of teaching aids and guidebooks, and 2) student perception sheets to determine students' responses to teaching aids and guidebooks. The results showed that the flow rate and water volume practicum teaching aids using the YF-S401 flow sensor along with the guidebook were feasible to use in the learning process.